Microbial Diversity Under the Influence of Natural Gas Storage in a Deep Aquifer - Ranchou-Peyruse, Magali; Guignard, Marion; Casteran, Franck; Abadie, Maïder; Defois, Clémence; Peyret, Pierre; Dequidt, David; Caumette, Guilhem; Chiquet, Pierre; Cézac, Pierre; Ranchou-Peyruse, Anthony (Frontiers in Microbiology, 2021)
Deep aquifers (up to 2 km deep) contain massive volumes of water harboring large and diverse microbial communities at high pressure. Aquifers are home to microbial ecosystems that participate in physicochemical balances. These microorganisms can positively or negatively interfere with subsurface i) energy storage (CH4, H2), ii) CO2 sequestration; and iii) resource (water, rare metals) exploitation. The aquifer studied here (720 m deep, 37 °C, 88 bar) is naturally oligotrophic, with a total organic carbon content of <1 mg.l-1 and a phosphate content of 0.02 mg.l-1. The influence of natural gas storage locally generates different pressures and formation water displacements, but it also releases organic molecules such as monoaromatic hydrocarbons at the gas/water interface. The hydrocarbon biodegradation ability of the indigenous microbial community was evaluated in this work. The in situ microbial community was dominated by sulfate-reducing (e.g., Sva0485 lineage, Thermodesulfovibriona, Desulfotomaculum, Desulfomonile and Desulfovibrio), fermentative (e.g., Peptococcaceae SCADC1_2_3, Anaerolineae lineage and Pelotomaculum), and homoacetogenic bacteria (“Candidatus Acetothermia”) with a few archaeal representatives (e.g., Methanomassiliicoccaceae, Methanobacteriaceae, and members of the Bathyarcheia class), suggesting a role of H2 in microenvironment functioning. Monoaromatic hydrocarbon biodegradation is carried out by sulfate reducers and favored by concentrated biomass and slightly acidic conditions, which suggests that biodegradation should preferably occur in biofilms present on the surfaces of aquifer rock, rather than by planktonic bacteria. A simplified bacterial community, which was able to degrade monoaromatic hydrocarbons at atmospheric pressure over several months, was selected for incubation experiments at in situ pressure (i.e., 90 bar). These showed that the abundance of various bacterial genera was altered, while taxonomic diversity was mostly unchanged. The candidate phylum Acetothermia was characteristic of the community incubated at 90 bar. This work suggests that even if pressures on the order of 90 bar do not seem to select for obligate piezophilic organisms, modifications of the thermodynamic equilibria could favor different microbial assemblages from those observed at atmospheric pressure.